IgG antibodies from dourine infected horses identify a distinctive Trypanosoma equiperdum antigenic pattern of low molecular weight molecules - Luciani, M.; Pancrazio, C. Di; Febo, T. Di; Tittarelli, M.; Vulpiani, M.P.; Puglielli, M.O.; Naessens, Jan; Sacchini, F. (Elsevier, 2013)
Diagnosis and control of dourine is strongly based on serological evidence, but knowledge of the humoral response of horses during infection is limited. In this study we developed a chemiluminescent immunoblotting (cIB) assay to characterise the Trypanosoma equiperdum antigen pattern recognised by IgGs from naturally or experimentally dourine-infected horses and analyse the kinetics of IgG humoral response following the infection. One compounding factor is that sera from uninfected animals often cross-react with T. equiperdum antigens. Development of the cIB assay was based on the hypothesis that serum IgGs from healthy and infected animals recognise different T. equiperdum antigen patterns. We used sera from 8 naturally infected horses which had recovered from Italian outbreaks and 2 experimentally infected mares. In addition, sera from 10 healthy control animals, eight of which were CFT positive but IFA negative for dourine, were collected from disease free regions. Sera were compared by the complement fixation test (CFT), indirect immune fluorescence (IFA) and the cIB assay. cIB analysis revealed that IgGs from infected horses, in contrast to IgGs from healhty horses, specifically recognise a T. equiperdum antigenic profile with low molecular weight bands ranging between 16 and 35 kDa. A time course experiment indicated that IgGs specific for the 16-35 kDa parasite protein fraction appear 17 days post-infection. The cIB assay confirmed all ten infected animals as positive and all controls as negative. This study demonstrated that analysis of IgGs by cIB can provide clear confirmation of trypanosome infection in horses, suggesting that this technique can be applied as a confirmatory serological test for dourine infection.